Mixed-Media Directing Technique and the Salvation of Theatre-Going Culture: The Aesthetics of Contemporary Theatre in Nigeria - Olatunji, Olalekan F. (Academia Journal of Humanities & Social Sciences, 2025)
The theatre has witnessed several technological modifications, which include the incorporation of mixed-media elements into the live performance, but despite this innovation, the Nigerian theatre-going culture pitiably continues to fall. This is traced to the slow response of directors to the surge in the audiences’ aesthetic taste and the delivery of the contemporary live show. However, some directors, such as Bolanle Austen-Peters and Tayo Isijola in “Wakaa the Musical” and Julie Okoh’s The Trials respectively, have experimented with and prophesied the inclusion of mixed-media elements as a sustainable technique for contemporary theatre directing. This study engages Hans-Thies Lehmann’s post-dramatic theatre and Oreofe Williams’ ‘Artotech’, which emphasises the necessary connection of the theatre with the changing media of the current century as a theoretical framework. The descriptive study recommends the mixed-media technique engaged in the performances under study as a viable technique to increase audience participation and sustain theatre-going in Nigeria.